Ruqyah Practice and Commodification of Spirituality on Tiktok @Nyairosidah3 Account - Fikriyah, Anisa Nur; Clareta , Dyva (KURIOSITAS: Media Komunikasi Sosial dan Keagamaan, 2025)
The phenomenon of ruqyah carried out online through the TikTok platform shows the transformation of religious practices in the digital media era. This study aims to analyze the phenomenon of ruqyah practices in live streams of TikTok @nyairosidah3 accounts and examine the interactions that arise between ruqyah practitioners (Nyai Rosidah) and netizens that reflect the process of religious commodification. This research uses a qualitative approach with a content analysis method. Data were obtained from 30 live broadcast sessions observed during the period 1–30 March 2025 and analyzed thematically. The results of the study show that interactions in live broadcasting can be categorized into four main categories, namely positive comments, negative comments, ruqyah requests, and responses from ruqyah perpetrators. Positive comments came from individuals who experienced mental health disorders such as anxiety and physical tension, who then gave testimonials after receiving ruqyah services via live streaming. The request for ruqyah conveyed through the comment column shows that the digital space has become a medium for remote spiritual consultation. The responses given in the form of scripture readings and simple instructions to the patient reflect empathic interpersonal communication. This study uses the theory of computer-mediated communication to understand the form of virtual interaction that exists without physical presence, as well as the theory of religious commodification to examine how spiritual values are displayed and interpreted in the context of digital media. These findings suggest that religious practices in social media are not only ritualistic, but also part of symbolic and economic exchanges in digital media.